2009
DOI: 10.1111/j.1365-2966.2009.15117.x
|View full text |Cite
|
Sign up to set email alerts
|

The size distribution of void filaments in a ΛCDM cosmology

Abstract: The size distribution of minifilaments in voids has been derived from the Millennium Run halo catalogues at redshifts z= 0, 0.5, 1 and 2. It is assumed that the primordial tidal field originated the presence of filamentary substructures in voids and that the void filaments have evolved only little, keeping the initial memory of the primordial tidal field. Applying the filament‐finding algorithm based on the minimal spanning tree (MST) technique to the Millennium voids, we identify the minifilaments running thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…While it produces distinct structures, there is no clear oneto-one connection between these objects and the branches of the network. A different approach involves the use of minimal spanning tree algorithms for the segmentation of the filament network into main and secondary branches (Colberg 2007;Park & Lee 2009). It gives a very good separation of the global network into distinct objects, but it can also introduce unwanted artefacts (for details see Colberg 2007).…”
Section: Segmenting the Filamentary Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…While it produces distinct structures, there is no clear oneto-one connection between these objects and the branches of the network. A different approach involves the use of minimal spanning tree algorithms for the segmentation of the filament network into main and secondary branches (Colberg 2007;Park & Lee 2009). It gives a very good separation of the global network into distinct objects, but it can also introduce unwanted artefacts (for details see Colberg 2007).…”
Section: Segmenting the Filamentary Networkmentioning
confidence: 99%
“…The Park & Lee (2009) study offers an interesting comparison point since it analysed the number and properties of filaments found in void regions. As expected, given that they focused on void regions, Park & Lee (2009) found a smaller number of filaments at all L values.…”
Section: Spatial Extent Of Filamentsmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, previous work has shown that a lot of potentially observable statistical properties of voids are directly to the primordial tidal field (e.g. Lee & Park 2006; Platen, van de Weygaert & Jones 2008; Park & Lee 2009a,b). However, questions may be raised by the direct use of the formula Doroshkevich (1970), as they applied it in Millennium Simulation.…”
Section: The Void Finder By Orbit Reconstructionmentioning
confidence: 99%
“…Other authors define filaments as structures that connect massive halos and are traced by other, lesser massive, halos, disregarding the existence of a saddle point between them (e.g. Alpaslan et al 2014;Park & Lee 2009). There are works that are based on visual inspection (Akamatsu et al 2017), identification of regions inter-clusters (Pimbblet et al 2004;Colberg et al 2005), or on a random configuration of galaxies based on a modelled probability distribution (Tempel et al 2014a).…”
Section: Introductionmentioning
confidence: 99%